Investigating the phosphinic acid tripeptide mimetic DG013A as a tool compound inhibitor of the M1-aminopeptidase ERAP1. (15th June 2021) - Wilding, Birgit; Pasqua, A. Elisa; E. A. Chessum, Nicola; Pierrat, Olivier A.; Hahner, Tamas; Tomlin, Kathy; Shehu, Erald; Burke, Rosemary; Richards, G. Meirion; Whitton, Bradleigh; Arwert, Esther N.; Thapaliya, Arjun; et al.
Graphical abstract: Abstract: ERAP1 is a zinc-dependent M1-aminopeptidase that trims lipophilic amino acids from the N -terminus of peptides. Owing to its importance in the processing of antigens and regulation of the adaptive immune response, dysregulation of the highly polymorphic ERAP1 has been implicated in autoimmune disease and cancer. To test this hypothesis and establish the role of ERAP1 in these disease areas, high affinity, cell permeable and selective chemical probes are essential. DG013A 1, is a phosphinic acid tripeptide mimetic inhibitor with reported low nanomolar affinity for ERAP1. However, this chemotype is a privileged structure for binding to various metal-dependent peptidases and contains a highly charged phosphinic acid moiety, so it was unclear whether it would display the high selectivity and passive permeability required for a chemical probe. Therefore, we designed a new stereoselective route to synthesize a library of DG013A 1 analogues to determine the suitability of this compound as a cellular chemical probe to validate ERAP1 as a drug discovery target.